Enhanced Physiological Stress Response in Patients with Normal Tension Glaucoma during Hypoxia - Line Marie Dalgaard; Jeppe Vibæk; Rupali Vohra; Lars Thorbjørn Jensen; Barbara Cvenkel; Niels H. Secher; Niels Vidiendal Olsen; Miriam Kolko (Journal of Ophthalmology)
Purpose. To investigate whether patients with normal tension glaucoma (NTG) show an enhanced stress response to reduced oxygen supply compared to age-matched healthy controls, measured by serum adrenaline and endothelin-1 (ET-1) levels and changes in distal finger temperature. Methods. A thorough clinical characterization of patients with NTG and age-matched controls was performed prior to inclusion in the study. Twelve patients with NTG and eleven healthy controls met the inclusion criteria and were enrolled in the study. All subjects underwent a two-day investigation. Participants were randomly exposed to either hypoxia or normoxia during the first visit. Hypoxia or normoxia was induced for two hours through a tightly fitting face mask. In addition, the peripheral circulation was assessed with a thermographic camera. Blood samples were obtained before, during, and after hypoxia or normoxia to evaluate systemic stress molecules such as catecholamines and ET-1 levels. Results. In patients with NTG, reduced oxygen supply induced an increase in peripheral blood adrenaline (p < 0.05) and a decrease during recovery (p < 0.01). A difference in distal finger temperature was shown in patients with NTG under hypoxia compared to normoxia (exposure: p < 0.05; recovery: p < 0.05). Hypoxia induced an increase in peripheral blood ET-1 levels in both groups (NTG: p < 0.01; controls: p < 0.05). Conclusion. Patients with NTG had an enhanced physiological stress response as a consequence of hypoxia compared with age-matched controls. Although more studies are needed, the present study supports the involvement of vascular risk factors in the pathophysiology of NTG.